Research for development: evidence-based hilsa management improvements in Myanmar - Akester, Michael; Bladon, Annabelle; Conallin, John (Frontiers in Marine Science, 2024)
The hilsa (Tenualosa ilisha) fishery in Myanmar is of importance as it provides an income for around 1.6 million artisanal low-income fisher households and generated USD 237.32M in export earnings from 156,000 metric tons in 2021. Fisheries Performance Indicator assessments have shown that the fishery, both artisanal and industrial, is close to economic collapse. Research was undertaken to find ways to improve the management of the fishery including studies to establish the migration routes and spawning periodicity of hilsa in addition to socioeconomic assessments and business case valuations to recommend finance mechanisms for improved management and maintenance of the fishery. Results indicate that the closed season for hilsa fishing misses the main spawning period in September. In addition, the chemical analysis of hilsa otoliths shows the importance of upstream spawning grounds – some 800km from the sea. Recommendations were made, and enacted March 2022, regarding the need for a new September closed season in addition to no-take hilsa sanctuaries along the main migration routes. A value was placed on the hilsa fishery at close to USD800M per annum. A USD100M annual investment cost is suggested to ensure that the new and old closed seasons are respected by licensed and unlicensed fishers. This investment could be generated by recommended fiscal reforms to provide incentives for fishers to respect the new fishing restrictions. Transboundary fisheries management opportunities are being advanced by informal tripartite scientific collaboration between Bangladesh, India and Myanmar. Social aspects, involving fisheries co-management with artisanal fisher communities and local government authorities, need to be continued to demonstrate the benefits of improved fisheries management in terms of the expected sustainable yields and a move away from potential economic fishery collapse.